La consulta previa a los pueblos indígenas de Colombia (2014)
The Consultation is a fundamental right of indigenous communities in Colombia; their recognition was a hard process, result of struggles and sacrifices.The Colombian State ratification of the 169 convention through the Law 21 of 1.991 represents for indigenous communities the opportunity by many years denied about their culture and territory protection. The Consultation involves the exercise of other rights such as self-determination and participation.Despite the recognition by the Constitutional Court as a fundamental right, has been submitted gaps and irregularities in its implementation. There is not regulatory framework governing this mechanism effectively, there is no guarantee protection of indigenous peoples interest